Islamic Education Thought of Kh. Muhammad Kholil Bangkalan and It’s Implementation on Contemporary Generation - Asep Awaluddin (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2020)
This paper elaborates an Islamic Education thought of Kiai Kholil as Indonesian scholars. This study uses library research to reveal the thought and the role of Kiai Kholil in developing Islamic Education in the Nusantara. The result of this research showed KH. Muhammad Kholil goodly accepted with his methods of Islamic Education espicially in the Traditional Islamic Education. KH. Muhammad Kholil Bangkalan is needed to be a great example for contemporary generation. His journey of study is based on sincere of his heart, loving sciences and good attitude to the teachers. We can copy his spirit for contemporary generation to get succes in learning by concerned and prefer to take a part of humans quality empowerment.